Current and emerging therapies for localized high-risk prostate cancer. Issue 3 (4th March 2021) - Moris, Lisa; Devos, Gaëtan; Van den Broeck, Thomas; Milonas, Daimantas; Albersen, Maarten; Berghen, Charlien; De Meerleer, Gert; Devlies, Wout; Everaerts, Wouter; Gevaert, Thomas; Van Poppel, Hendrik; Claessens, Frank; et al.
ABSTRACT: Introduction : Despite progress in the field of high-risk localized prostate cancer (HRPCa) treatments, high-risk patients treated with curative intent are at increased risk of biochemical recurrence, metastatic progression and cancer-related death. The optimal treatment strategy remains a topic of debate. This review provides an overview of the current and investigational therapeutic options for HRPCa. Areas covered : A PubMed search was performed for papers on the current perspectives on the multimodality treatment of HRPCa. We focus on both primary local treatment as well as systemic treatment options. Finally, relevant ongoing trials focusing on systemic treatments (including [neo]adjuvant treatments) enrolling at least 50 patients were retrieved, to highlight ongoing research and treatment optimization. Expert opinion : Disease progression in HRPCa patients is driven by local tumor extension and subclinical metastases. Therefore, the main treatment concept is a multimodal approach targeting the primary tumor with extended surgery or RT with long-term ADT and simultaneously targeting micro-metastatic deposits. However, there is still room for optimization. Upcoming clinical trials comparing surgery versus RT as local treatment, trials with (neo)adjuvant chemotherapy or androgen receptor signaling inhibitors will likely change the treatment landscape. However, a multimodal treatment strategy will stay as the cornerstone in the treatment of HRPCa.